Informationally Redundant Utterances in Academic Texts - Ümit Deniz Turan (Dilbilim Araştırmaları Dergisi)
This study investigates Informationally Redundant Utterances (IRU) in Turkish academic texts written within the field of linguistics. IRUs are used to compensate readers’ cognitive limitations, such as the inability to automatically infer some logical conclusions derived from entailments, presuppositions and implicatures. Writers, therefore, do not take it for granted that the logical conclusions will be drawn online by their readers; instead they present the logical conclusions explicitly with IRUs to provide reader-friendly essays. Likewise, they use IRUs which they think are not salient enough for the readers to immediately retrieve from the memory: Thus, they use IRUs to bring old information to the readers’ focus of attention. Results also show that IRUs interact with the local and global levels of discourse structure in interseting ways.